The Ranking Function for fuzzy parameters of Rayleigh Distribution (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This research deals with estimating the parameters for the generalized Rayleigh distribution depending on the maximum likelihood estimator method.Employing the real data to obtain the confidence intervals estimation for all parameters in generalized Rayleigh distribution. Fuzzy numbers will be construct from the trapezoidal membership function for this confidence interval of all parameters. Finally the ranking function algorithm using to convert the fuzzy numbers in to crisp (trapezoidal) fuzzy numbers and its applied to find the probability density function and survival function.